Computational thinking in teacher digital competence frameworks - Loureiro, Ana Cláudia (2022)
Several western countries have introduced educational policies to keep up with needs and demands of the digital society. Digital competence frameworks, particularly for the teaching profession, may fit into this context, which also includes the development of computational thinking, a competency construct that many consider necessary for the empowerment of citizens. The analysis of the approach to computational thinking in these references provides information on competences that need to be contextualised in the framing of the concept, to ensure conditions for its integration in the educational environment. This analysis is the aim of this study, focusing on four frameworks guiding teacher education policies: Standards of ICT competence for teachers (UNESCO), Common Framework for Teaching Digital Competence (INTEF, Spain), European framework for the digital competence of educators: DigCompEdu (EU) and ISTE Standards for Educators: A Guide for Teachers and Other Professionals (ISTE, USA). Content analysis was used as methodology. Results show that there is no consensus on the definition of computational thinking, although the frameworks, implicitly or explicitly, recognize the importance of integrating computational thinking in teaching practice. However, there is no evidence of methodological guidelines for the operationalization of digital teaching skills that can ensure the promotion of computational thinking.